Ultrassom em pós-colheita de uvas Isabel e Cabernet Sauvignon: influência sobre a composição fenólica da fruta, suco e vinho - Comarella, Carine Glaucia (2016)
Phenolic compounds are secondary metabolites widely distributed in the plant kingdom, where the grape stands out as an important available source of these substances. In this fruit and its derivatives, these compounds play an important role in the development of sensory characteristics, besides having pronounced antioxidant activity and can act in the prevention of various diseases. The content of phenolic compounds is dependent upon various edafoclimatic factors which grapes are subjected, and its degree of phenolic maturation along with the efficiency of the extraction process greatly affects the concentration of these substances in juice and wine. Ultrasound is an emerging technology that has a range of applications and advantages in the food industry, having among its main uses, facilitating the extraction of plant compounds. More recently, its use has been evaluated in post-harvest of fruits and vegetables as possible elicitor agent capable of promoting the synthesis of phenolic compounds. Thus, this study aimed to evaluate the performance of ultrasound in the postharvest treatment of Isabella and Cabernet Sauvignon grapes, about the effects on the extractability of fruit phenolic compounds and corresponding concentration in juices and wines. For that were tested different ultrasound application times (3, 5, 7, and 10 minutes) in grapes from 2013, 2014 and 2015 harvests and analyzed the time required for observing the response in each treatment used. In fruit maturation phenolic analysis was performed by evaluating the extractability and concentration of phenolic compounds. In the fruit was performed analysis of phenolic maturation by evaluating the extractability and concentration of phenolic compounds. In Isabel grape juice and Cabernet Sauvignon wine the phenolic compounds were evaluated and color indices, anthocyanin identification juice by HPLC/DAD/MS and quantitative descriptive sensory analysis of wine. The results showed that the effects of ultrasound are dependent of time applied, which also influences the period required to initiate the response. In Isabella cultivar grapes was more sharply observed the effect of treatment on extractability. This can be improved depending on the ultrasound conditions of application, resulting in a substantial increase in anthocyanin content of the juice. The phenolic potential data of Isabella grapes also suggest a possible elicitor effect of ultrasound, i.e., synthesis stimulation of phenolic compounds. In juice of this cultivar 33 anthocyanins have been identified, among which 5 aglycones, mono and diglucosilated, as well as acylated compounds, direct or mediated by acetaldehyde condensation products, and pyranoanthocyanins. The results showed more influence of ultrasound on concentration than on the profile of these pigments. In Cabernet Sauvignon grapes, ultrasound can lead to significant degradation of fruit anthocyanins, which reflects in their wine. In this product, generally the ultrasound did not appear to promote better sensory quality or acceptance of the wine, but in certain doses increased the intensity of aromas such as red fruit. The monitoring of the different harvests showed that the state of fruit maturation influences the response to ultrasound, since the behavior to the treatments is not always repeated over the years.